2021
DOI: 10.1088/1402-4896/ac1eb0
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical investigation on the quarter-wavelength model — part 1: analysis

Abstract: The quarter-wavelength-mode has been widely used in microwave absorption material research for many years. Based on wave-cancellation method, it is proved in the first part of this work that the model fails for most cases. It is interesting that the principles underlining this work are not beyond those covered by fundamental college courses even though the improper model has been dominant in the field for long without correction. In the second part of this work, the correctness of results obtained are verified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(68 citation statements)
references
References 41 publications
(53 reference statements)
4
64
0
Order By: Relevance
“…We have previously shown that the minima of |RL(x1 -)| can be described accurately using wave cancellation theory WCT [7,8] and as a consequence, we qualitatively identified the flaws in the QWM [7,12,19]. Here, we verify the results of WCT using quantitative mathematics based on our own experimental data obtained from the film of composite BaFe 11.8 Ce 0.2 O 19 /polypyrene [25], as shown in Fig.…”
Section: A Quantitative Verification Of the Theoretical Results From ...supporting
confidence: 70%
See 4 more Smart Citations
“…We have previously shown that the minima of |RL(x1 -)| can be described accurately using wave cancellation theory WCT [7,8] and as a consequence, we qualitatively identified the flaws in the QWM [7,12,19]. Here, we verify the results of WCT using quantitative mathematics based on our own experimental data obtained from the film of composite BaFe 11.8 Ce 0.2 O 19 /polypyrene [25], as shown in Fig.…”
Section: A Quantitative Verification Of the Theoretical Results From ...supporting
confidence: 70%
“…The results conform to the inverse relationship needed to replace QWM [7,12,19,27]. If α P d is small, beams 3 r , 4 r , 5 r , etc.…”
Section: A Quantitative Verification Of the Theoretical Results From ...supporting
confidence: 69%
See 3 more Smart Citations